2023
DOI: 10.1002/anie.202300962
|View full text |Cite
|
Sign up to set email alerts
|

One‐Step Calcination Synthesis of Bulk‐Doped Surface‐Modified Ni‐Rich Cathodes with Superlattice for Long‐Cycling Li‐Ion Batteries

Abstract: Nickel‐rich (Ni≥90 %) layered cathodes are critical materials for achieving higher‐energy‐density and lower‐cost next‐generation Li‐ion batteries (LIBs). However, their bulk and interface structural instabilities significantly impair their electrochemical performance, thus hindering their widespread adoption in commercial LIBs. Exploiting Ti and Mo diffusion chemistry, we report one‐step calcination to synthesize bulk‐to‐surface modified LiNi0.9Co0.09Mo0.01O2 (NCMo90) featuring a 5 nm Li2TiO3 coating on the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 53 publications
(84 reference statements)
0
16
0
Order By: Relevance
“…The lattice fringes of the coating layer (Figure B II ) with a d -spacing of 0.225 nm coincide well with the (2̅02) planes of the Li 2 ZrO 3 phase ( C2/c space group) . The subsurface nanolayer is attributed to the Al/Zr-rich rocksalt phase (superlattice) with a d -spacing of 0.238 nm (Figure B III ), stabilizing the delithiated layered structure . High-resolution energy-dispersive spectroscopy (EDS) mappings show the diffusion depth of Al and Zr elements, in which the Al element diffused into the bulk of SC811, and the Zr element enriched in the surface (Figure C).…”
mentioning
confidence: 73%
See 3 more Smart Citations
“…The lattice fringes of the coating layer (Figure B II ) with a d -spacing of 0.225 nm coincide well with the (2̅02) planes of the Li 2 ZrO 3 phase ( C2/c space group) . The subsurface nanolayer is attributed to the Al/Zr-rich rocksalt phase (superlattice) with a d -spacing of 0.238 nm (Figure B III ), stabilizing the delithiated layered structure . High-resolution energy-dispersive spectroscopy (EDS) mappings show the diffusion depth of Al and Zr elements, in which the Al element diffused into the bulk of SC811, and the Zr element enriched in the surface (Figure C).…”
mentioning
confidence: 73%
“…39 The subsurface nanolayer is attributed to the Al/Zr-rich rocksalt phase (superlattice) with a d-spacing of 0.238 nm (Figure 2B III ), stabilizing the delithiated layered structure. 40 High-resolution energy-dispersive spectroscopy (EDS) mappings show the diffusion depth of Al and Zr elements, in which the Al element diffused into the bulk of SC811, and the Zr element enriched in the surface (Figure 2C). The quantitative distribution information of Al and Zr elements based on EDS analysis further reveals that Zr enriches in the (sub)surface region (≤80 nm), and Al enriches in the bulk phase region (Figures S7, S8), which is consistent with the results of Ar + sputtering-assisted X-ray photoelectron spectroscopy (XPS) (Figure S9).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Serving as the pivotal component that influences the performance and cost of lithium-ion batteries, nickel-rich cathode materials are widely used for their superior reversible specific capacity and acceptable cost. Nevertheless, the nickel-rich cathode is still confronted with the problem of capacity degradation and poor thermal stability caused by interfacial instability in practical applications. Recent studies have shown that the development of a concentration-gradient cathode serves as a potent method for optimizing the capacity and cycle stability of a high-nickel cathode. In the secondary particles featuring a gradient structure, the nickel concentration gradually decreases from the inner core to the outer surface, while the manganese content increases steadily . The Ni-rich fraction in the inner core ensures a high specific capacity, while the Mn-rich fraction in the outer layer reduces the surface reactivity and exhibits high thermal stability .…”
Section: Introductionmentioning
confidence: 99%